Pengaruh Kepemilikan Manajerial dan Kepemilikan Asing terhadap Kinerja Perusahaan di Sektor Perdagangan, Jasa dan Investasi - Rindu Kurniawati; Rahman Anshari; Yulia Tri Kusumawati (Jurnal Simki Economic, 2025)
This study aims to empirically examine the effect of managerial ownership and foreign ownership on company performance. Secondary data from 208 annual financial reports of companies in the trade, services, and investment sectors for the period 2021–2023 are used as panel data and analyzed using multiple linear regression, with Return on Assets (ROA) as a performance indicator. The results of the study indicate that managerial ownership and foreign ownership have no effect on company performance. Theoretically, these results indicate that ownership structure is not the main factor in driving performance, thus contributing to the development of governance theory in developing countries. Practically, these results serve as a reference for stakeholders to consider other more relevant factors in performance improvement strategies.